Comparison of the Biological Activity of Crude Polysaccharide Fractions Obtained from Cedrela sinensis Using Different Extraction Methods - Oh Min Hui; Yoon Kyung Young (Polish Journal of Food and Nutrition Sciences)
Four preparations of crude polysaccharides were obtained from Cedrela sinensis using four methods of extraction, and finally precipitation with ethanol. Hot-water and processes assisted by ultrasound and enzymes (Shearzyme or Viscozyme) were carried out. The yield of polysaccharide fraction extracted with the enzyme-assisted method using Shearzyme (P-EAS) was the highest at 10.53%. All crude saccharides were composed of six monosaccharides including arabinose, galactose, glucose, mannose, rhamnose, and xylose. Crude polysaccharide fraction extracted by hot water showed the highest DPPH• and ABTS•+ scavenging activities as well as α-amylase inhibitory activity. All fractions showed higher retardation effects on glucose and bile acid absorption using the in vitro dialysis system compared to the control (without polysaccharide fraction); specifically, the glucose retardation index of P-EAS was similar to that of carboxymethylcellulose. Overall, crude polysaccharide fractions obtained from C. sinensis can be used as functional ingredients owing to their excellent functional properties.